Conduction Response in Highly Flexible Nonvolatile Memory Devices. (13th April 2020) - Ren, Shuxia; Li, Zhenhua; Tang, Lingzhi; Su, Xiao; Zhang, He; Zhang, Guanglei; Zhang, Han; Cao, Guozhong; Zhao, Jinjin
Abstract: Resistive random access memories (RRAMs) are promising candidates for future nonvolatile memories. Here, a flexible nonvolatile resistive switching (RS) device is constructed by spin coating an RS film of graphene oxide (GO) incorporating with TiO2 nanoparticles, denoted as TGO, on an indium‐doped tin oxide electrode. The TGO film is highly flexible and optically transparent (92–98%), and the device demonstrates excellent RS characteristics (centralized SET and RESET voltages and large RS ratio) at a low voltage of 0.5 V. The RS behavior is found to originate from the migration and distribution of oxygen anions in the TGO film under an electric field. The oxygen anions extracted from TiO2 nanoparticle provide good chemical linkage for the development of sp 2 filaments in the GO film, promoting the RS behavior. The findings of this study may also be very useful for researchers working on controlling magnetism in RRAM devices. Abstract : A highly flexible and optically transparent nonvolatile memory device is fabricated by incorporating TiO2 nanoparticles into the graphene oxide film. The migration and distribution of oxygen anions provide good chemical linkage for the development of sp 2 filaments, promoting resistive switching behavior.